2014
DOI: 10.1086/676828
|View full text |Cite
|
Sign up to set email alerts
|

Two Aspects of the Rural-Urban Divide and Educational Stratification in China: A Trajectory Analysis

Abstract: Contextualized in China’s social change of the past half-century, this paper develops the notion of dichotomous inequality to conceptualize the two aspects of China’s rural-urban divide in educational inequality—the household registration system (hukou) assigns people to a top-bottom hierarchy, and the rural-urban schooling system institutionalizes unequal resource distribution and diverse school mission. Based on this conceptualization, we formulate a Chinese version of the maximally maintained inequality (MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 35 publications
(43 reference statements)
1
34
0
2
Order By: Relevance
“…Moreover, Liu's separate study also suggested that the demographic policy, namely, the 'one-child' policy, played an essential role in determining students' opportunities in elite universities (Liu, 2015). Contrary to the MMI theory, Hao et al's study, which is based on the data from the 2008 Chinese General Social Survey (CGSS), shows an 'accumulative penalty' effect of both rural hukou status and rural schooling on the students' chances of advancing their educational careers even the educational opportunities expand at all levels (Hao et al, 2014). analyze the patterns of public attitude and support regarding tuition, and they found that the middle class families show strong support for the fees and even differentiated fees for different fields of study, whereas working-class students were very concerned about the fees and implications on the students' debt.…”
Section: The Maximally Maintained Inequalitymentioning
confidence: 98%
“…Moreover, Liu's separate study also suggested that the demographic policy, namely, the 'one-child' policy, played an essential role in determining students' opportunities in elite universities (Liu, 2015). Contrary to the MMI theory, Hao et al's study, which is based on the data from the 2008 Chinese General Social Survey (CGSS), shows an 'accumulative penalty' effect of both rural hukou status and rural schooling on the students' chances of advancing their educational careers even the educational opportunities expand at all levels (Hao et al, 2014). analyze the patterns of public attitude and support regarding tuition, and they found that the middle class families show strong support for the fees and even differentiated fees for different fields of study, whereas working-class students were very concerned about the fees and implications on the students' debt.…”
Section: The Maximally Maintained Inequalitymentioning
confidence: 98%
“…Focusing on younger learners, however, could help to give momentum to their educational trajectories. This is not to exclude older learners from benefiting from the funds of knowledge concept 5 , but to underscore the need to begin socially just learning at a young age in order to better combat cumulated disadvantage (Hao et al, 2014). This need is also supported by the fact that most funds of knowledge projects focus on primary learners (Hogg, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The hukou system has also been identified as a mechanism for perpetuating inequality between urban and rural spheres by creating "two types of citizenship in a single country" (Hao, Hu, & Lo, 2014). Since 2009, however, reform in Shanghai has permitted city-born migrant children to attend the same public and private schools as urban-hukou Chinese children (Chen & Feng, 2013).…”
Section: City-born Migrant Childrenmentioning
confidence: 99%
“…Dismantling the rigid household registration system can be served as the first step to mitigate the inequality of basic education. "The Hukou dichotomy and the rural-urban school dichotomy are two major forces of educational inequality in China [26]." The residential permit system (Hukou System) was inherited in the process of urbanization, and it also influenced the rural-urban educational inequality.…”
Section: Inequality Of Policy Formationmentioning
confidence: 99%